1997
DOI: 10.1046/j.1365-2648.1997.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with dizziness: an explorative study

Abstract: A qualitative study was conducted for the purpose of exploring how patients with dizziness manage their daily living. Ten patients with history of dizziness were recruited from the out‐patient clinic, Department of Audiology, in a hospital in Stockholm. Collection and analysis of data were inspired by the method of grounded theory. Four themes were developed that described the experience of living with dizziness: vulnerable reactions, affirmation and non‐affirmation, finding ways to carry on daily living, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
4
14
0
Order By: Relevance
“…Some individuals reported feeling isolated because of an abundance of avoidance behaviours. This observation agrees with other studies on disability in which people with dizziness often avoid different activities, environments and situations that are perceived as difficult and that increase symptom burden [44,45].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Some individuals reported feeling isolated because of an abundance of avoidance behaviours. This observation agrees with other studies on disability in which people with dizziness often avoid different activities, environments and situations that are perceived as difficult and that increase symptom burden [44,45].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies on people with dizziness contain descriptions of how these people feel vulnerable when walking among strangers because of fear of being seen as drunk as the result of an unsteady gait [44,46]. This finding concurs with results from our study showing that all focus groups and the individual interview contained accounts of how the participants' self-efficacy decreased in contexts where they felt nervous about being seen as drunk.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the effectiveness of individualized nursing interventions is not clearly proven and it is suggested that they be tested in a variety of contexts with patient outcomes in focus, and not only utilization of health care services, clinical status, or adherence to treatment (Frich, 2003;Suhonen et al, 2008). Patients with peripheral vestibular disorders have reported that they felt very vulnerable and emphasized the importance of affirmation from health care professionals (Mendel, L€ utz en, Bergenius, & Bj€ orvell, 1997). The patients expressed needs for information, for practical advice on how to adapt to this new life situation, and for continuity in care (Mendel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with peripheral vestibular disorders have reported that they felt very vulnerable and emphasized the importance of affirmation from health care professionals (Mendel, L€ utz en, Bergenius, & Bj€ orvell, 1997). The patients expressed needs for information, for practical advice on how to adapt to this new life situation, and for continuity in care (Mendel et al, 1997). From this knowledge, we developed a comprehensive interdisciplinary intervention program that combines an educationally structured program with individualized nursing support.…”
Section: Introductionmentioning
confidence: 99%